Ultrasound‐guided peripheral trunk block technique: A new approach gradually stepping onto the stage of clinical anesthesia. Issue 3 (28th September 2021) - Liu, De‐Xing; Zhu, Zhao‐Qiong
Abstract : In recent years, with the continuous development and validation of new visualization, the ultrasound‐guided peripheral trunk block becomes more mature and has a more extensive and broader implementation scope in clinical anesthesia. Based on this, we reviewed and summarized the literature on peripheral trunk nerve block include: paraspinal block, retrolaminar block, plane block of erect spinal muscle, transverse convex to pleural midpoint block, block of the trapezius muscle and anterior serratus muscle, anterior serratus muscle block, thoracic nerve block, abdominal transverse fascia block, type‐I block of quadratus lumborum, type‐II block of quadratus lumborum, type‐III block of quadratus lumborum, block of the sheath of rectus abdominis. This paper reviews the ultrasound‐guided peripheral trunk block technique, including development history, anatomic basis, implementation methods, advantages and disadvantages of nerve block technique, and describes the bottleneck and difficulties of nerve block technique at present.